13 curses / 2. - Harrison, Michelle, 1979- (Thirteen Treasures, 2012)
When fairies steal her brother, thirteen-year-old Rowan Fox promises that in exchange for his return she will find the thirteen charms that the fairies have enchanted and hidden in the human world.